Numerical and Experimental Investigation of the Mechanical Behavior of Cable-Supported Barrel Vault Structures with Varying Temperature - Guojun Sun; Mingze Wu; Zhihua Chen; Suduo Xue (Advances in Civil Engineering)
The cable-supported barrel vault (CSBV) structure system is a new type of hybrid spatial steel structure based on a beam string structure (or truss string structure), suspendomes, and cylindrical lattice shells. Steel cables (e.g., steel wire rope cables, steel strand cables, semiparallel steel tendons, and steel rods) are key components of CSBV structures. However, they have different elastic moduli and thermal expansion coefficients. In this study, the roof of a textile workshop (the first CSBV structure in China) was analyzed with four types of cables under the effect of varying temperature. Under half-span loading and full-span loading, the structural internal force and displacement at varying temperatures were obtained from finite element models employing four different types of steel cables. The internal force, displacement, and horizontal arch thrust changed linearly with increasing temperature. Moreover, the dynamic characteristics of CSBV with varying temperature were analyzed. The frequency of the CSBV changed linearly with increasing temperature. Based on the dynamic characteristics of CSBV with varying temperature, a seismic response time-history analysis was performed. The variation in the maximum responses of the internal force, displacement, and horizontal arch thrust was obtained. In each case, the mechanical behavior of the CSBV with semiparallel steel tendon cables was strongly affected by the temperature. Therefore, semiparallel steel tendons are not recommended as components of CSBV in cases where large temperature changes can be expected. Thereafter, a scale model of a CSBV was designed and used for experiments and corresponding finite element analyses under varying temperature. Experimental results show that the finite element method is effective for analyzing the mechanical behavior of CSBV under varying temperature.